PROJECT-BASED LEARNING, LEARNING STYLES, & CAMPUS ENVIRONMENT AS PREDICTORS OF PASSAGE PLANNING COMPREHENSION - Bayu Yudho Baskoro; Rizal Rochmansyah; Langandriansyah Dwi Yatno; Syafni Yelvi Siska; Adhi Pratistha Silen (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study investigates the effects of Project-Based Learning and learning styles on students’ comprehension of passage planning, with campus environment as a moderating variable. The research was conducted among Nautical Study Program students from Politeknik Pelayaran Sumatera Barat and Politeknik Ilmu Pelayaran Semarang, involving Semester 2 and Semester 4 students. A quantitative causal-comparative design was employed, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 684 respondents selected through quota sampling. The results show that Project-Based Learning has a positive and significant effect on passage planning comprehension, learning styles also have a positive and significant effect, and campus environment directly influences passage planning comprehension. However, campus environment does not significantly moderate the relationship between Project-Based Learning and passage planning comprehension, nor between learning styles and passage planning comprehension. The findings indicate that active, student-centered learning and alignment with students’ preferred learning styles are important determinants of comprehension in maritime navigation learning. The study implies that maritime vocational institutions should strengthen project-based instructional strategies and provide learning experiences that accommodate diverse learning styles, while continuing to improve campus facilities and learning support systems to enhance students’ understanding of passage planning.